SLITRK2 as a prognostic and immunological biomarker in gastric cancer - Huiqiong Zhu; Hailin Xiong; Xuli Guo; Haojie Liao; Shuyi Zhang (Discover Oncology, 2024)
Abstract Background SLIT and NTRK-like protein 2 (SLITRK2) encodes a transmembrane protein that regulates neurite outgrowth. Some studies have demonstrated that SLITRK2 overexpressed in glioma. But the expression pattern, prognostic value and immunologic function of SLITRK2 in tumors remains unknown. Methods The expression pattern of SLITRK2 among pan-cancers was examined through the Cancer Genome Atlas (TCGA) and Genotype-Tissue Expression (GTEx). We analyzed the association between SLITRK2 expression level and tumor stage among pan-cancers. Kaplan–Meier survival analysis was utilized to investigate the prognostic relevance of SLITRK2 across 33 different types of cancers. Moreover, the correlations among SLITRK2 expression, immune cell infiltration, immunomodulatory related genes, tumor mutation burden (TMB), microsatellite instability (MSI) were evaluated. The relationship between SLITRK2 expression and crucial genes mutations was also illustrated. By using tissue microarray (TMA), the expression of SLITRK2 in 89 paired gastric cancer (GC) tissues was investigated. Results Our study indicated that SLITRK2 expression varied across cancers. Elevated SLITRK2 expression was positively related to advanced tumor stage, poor overall survival (OS) and reduced disease-free survival (DFS). Bioinformatic analyses underscore SLITRK2’s role in immune response, with its expression significantly tied to immune cell infiltration and marker expression. Based on TMA data, SLITRK2 expression level was positively associated with differentiation, lymph node metastasis, AJCC stage, TNM stage, and poor survival outcome in GC patients. Conclusion Our findings provided that SLITRK2 may function as a biomarker by regulating immune cell infiltration. In addition, we verified that high SLITRK2 expression was correlated with poor prognosis in GC.